TORREFACTION OF RUBBERWOOD WASTE: THE EFFECTS OF PARTICLE SIZE, TEMPERATURE & RESIDENCE TIME - Wulandari, Winny; Jahsy, Nursayyidah Ainun; Tandias, Adrian Hartanto; Rizkiana, Jenny; Rubani, Inga Shaffira; Saputera, Wibawa Hendra; Sasongko, Dwiwahju (Journal of Engineering and Technological Sciences, 2020)
Agriculture waste has created massive challenges over the last few decades and yet also opportunities. This work aimed to produce high-quality biochar from rubberwood waste with calorific properties close to subbituminous coal. Using a tubular vertical reactor, the effects of rubberwood particle size (wood chips and shredded wood), torrefaction temperature (220, 260, and 300 °C), and residence time (30, 60, and 90 minutes) on the quality of torrefied rubberwood were studied. The results showed that the mass loss of the rubberwood increased as the temperature increased. Also, the particle size and residence time increased due to excessive devolatilization. A higher fixed-carbon content and calorific value as well as lower moisture and volatile-matter content were achieved by increasing the torrefaction temperature and residence time in comparison to the untreated sample (raw rubberwood). The highest fixed-carbon content and calorific value were found to be 56.7% and 6313 kcal/kg, respectively, for the wood chip particles that were torrefied at 300 °C for 60 minutes. Based on the Van Krevelen diagram, torrefaction of woodchip rubberwood at 300 °C with a residence time of 60 minutes demonstrated the optimum condition to generate a product with properties that are close to those of subbituminous rank coal.